The Effect of Tax Relief Regulations on Dividend Policy of Publicly Listed Companies in Indonesia - Harapon Angun Kasogi; Zaäfri Ananto Husodo (Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the impact of tax relief regulations, effective since 2021, on the dividend policies of publicly listed companies in Indonesia. We use panel data covering a three-year period before and after the implementation of the tax relief. This study uses a total of 413 listed companies, resulting in 2489 observations over the six-year research period. Logit regression and fixed-effect regression analyses are employed to identify the effects on the number of companies distributing dividends and the total dividends distributed, with firm-specific characteristics used as control variables. The logit regression results indicate that tax relief does not lead to a significant increase in the number of companies distributing dividends. However, there is a significant increase in the dividend levels among dividend-paying companies. To further encourage dividend distribution, the government can optimize existing regulations by considering criteria for tax relief eligibility based on dividend distribution activities. These findings can also serve as a consideration for investors when constructing their portfolios and for companies when designing dividend policies.